Ultra-high-purity iron is a novel and very compatible biomaterial. (June 2020) - Khan, Luqman; Sato, Katsumi; Okuyama, Shinichi; Kobayashi, Takeshi; Ohashi, Kazumasa; Hirasaka, Katsuya; Nikawa, Takeshi; Takada, Kunio; Higashitani, Atsushi; Abiko, Kenji
Abstract: Metals and alloys are used widely in bone prosthetic materials, stents and dental tissue reconstructions. The most common materials are stainless steels and cobalt-chromium-nickel and titanium alloys. These alloys can be easily deformed but are hard to break. However, their affinity for cells and tissues is very low. In addition, they can sometimes provoke unexpected metal allergies. Iron is an abundant trace element essential for humans. However, excess amounts in particular of Fe 2+ ions are toxic. We previously succeeded in obtaining 99.9996% ultra-high-purity iron (ABIKO iron). The chemical properties of ABIKO iron are completely different from that of conventional pure iron. For example, the reaction rate in hydrochloric acid is very slow and there is barely any corrosion. Here, we found that, in the absence of any type of coating, mammalian cells could easily attach to, and normally proliferate and differentiate on, ABIKO iron. On the other hand, cell densities and proliferation rate of the surfaces of plates made from Co–Cr–Mo or Ti–6Al–4V were significantly reduced. In addition, several stress and iron response genes, HSP70, SOD1, ATM and IRP2 did not change in the cells on ABIKO iron, while these genes were induced with exogenous application of FeSO4 . Cells also secreted and fastened some organics on ABIKO iron. In vitro collagen binding assay showed that ABIKO iron binds higher amount of collagens. These findings highlight ABIKO iron as a novel biocompatible prosthetic material. Highlights: Ultra-high-purity iron (ABIKO iron: 99.9996% purity) enables attachment and growth of mammalian cells. Osteogenic and myotube differentiation were observed on ABIKO iron without surface coating. Stress response genes were not induced in the cells on ABIKO iron.